Implementasi Kebijakan Restrukturisasi Pembiayaan UMKM Terdampak Covid-19 dan Manajemen Risiko Force Majeure Pada PT. BPRS Ikhsanul Amal Gombong - Mukhsinun Mukhsinun; Sinta Nurikurnia (LABATILA : Jurnal Ilmu Ekonomi Islam, 2021)
The financing restructuring policy is a policy of providing concessions to customers in making financing installment loans, the aim of which is to help customers who have problems in installment loans. Of course, this has a reason why customers experience credit problems, namely the Covid-19 pandemic. This time the author will conduct research on MSME financing customers with problems due to force majeure or natural disasters due to the Covid-19 Pandemic. This pandemic has greatly affected the economic sector, MSMEs are the most affected because people's activities are limited to leaving the house, resulting in the income of MSME entrepreneurs dropping dramatically. Implementation of a policy of relaxation or restructuring of MSME financing affected by Covid-19 and force majeure risk management carried out by PT. BPRS Ikhsanul Amal Gombong is quite good, the process is fast, only waiting for ± 3 days, the submission process is easy and the policy is very helpful for MSME customers affected by Covid-19. Risk management implemented by PT. BPRS Ikhsanul Amal Gombong, which includes: Prudential Banking Principles (careful), Establishment of Allowance for Earning Assets (PPAP), Intensive Billing, Product Marketing Strategy, Guarantee Binding.